Enhancing spatiotemporal paleoclimate reconstructions of hydroclimate across the Mediterranean over the last millennium - Anchukaitis, Kevin; Touchan, Ramzi; Meko, David; Kherchouche, Dalila; Slimani, Said; Sivrikaya, Fatih; Ilmen, Rachid; Mitsopoulos, Ioannis; Stephan, Jean; Attieh, Jihad; Hasnaoui, Foued; Camarero, J. Julio; et al. (Springer Science and Business Media LLC, 2024)
The Mediterranean region is projected to experience severe drying trends and more extreme hydroclimate events as a consequence of anthropogenic climate change over the next century. In some places this signal may have already emerged from natural variability, but uncertainty in long-term paleoclimate reconstructions can be a significant challenge to the detection of the influence of rising CO2 on droughts. Here we provide expanded context for recent and future hydroclimate changes with a new high-resolution (0.5o) spatial reconstruction of the Palmer Drought Severity Index (PDSI) using a tree-ring network that spans much of the last millennium. This network provides new perspective on the existing Old World Drought Atlas (OWDA) and allows us to characterize differences between OWDA and our reconstruction. In light of the uncertainties we identify, we also reexamine previous conclusions about the severity of recent droughts in the context of earlier centuries. We find that, in both the western Mediterranean and the Levant, recent dry periods remain the worst in at least the last 500 years, but our assessment of the significance and confidence in this finding is affected by differences in the tree-ring networks used for the reconstructions. Long millennium-length hydroclimate reconstructions in the Mediterranean do provide the opportunity to understand variability and trends in the hydroclimate of the region, but extant uncertainties arising from the existing tree-ring chronology network and methodological choices call attention to locations that require further proxy collection, chronology updates, and statistical scrutiny.

Funding to develop the Mediterranean tree-ring network and climate reconstructions was provided by grants from the US National Science Foundation’s Earth System History (ESH) and Paleo Perspectives on Climate Change (P2C2) programs, AGS-075956, AGS-0758486, AGS-0317288, AGS-1103314, AGS-1103450, AGS-1501856.

Peer reviewed
Keywords: Dendrochronology; Hydroclimate; Drought; Uncertainty; [SHS] Humanities and Social Sciences; Megadrought; Mediterranean; 15. Life on land